Gender, transgender: Towards a two-dimensional notion of injustice (Andamios, Revista de Investigación Social, 2015)
Trans expressions represent bodies, identities, practices and experiences that subvert the heteronormative cultural patterns of signification which places them out of the limits of  intelligibility provided by the hegemonic culture. This article attempts to reflect on how the exclusions that impact on these expressions correspond to a bivalent form of injustice. Considering the two-dimensional model of  justice introduced by Nancy Fraser, i argue that marginalization devices that operate on transgender people have as their point of origin a low cultural value, and a political economy based on a sexuality founded division of labor.
Keywords: Transgender; justice; identity; gender; Argentina